Analisis Keamanan Aplikasi Fintech di Indonesia: Studi Kasus OVO, GoPay, ShopeePay dan Dana - Bertnardo Mario Uskono; Rian Wijaya; Mochamad Galih Pradipta; Aldiansyah Kusnadi (Journal of Informatic and Information Security, 2024)
This research analyzed the security of four leading digital wallet applications in Indonesia (OVO, GoPay, ShopeePay, and DANA) using the Mobile Security Framework (MobSF) to identify potential user data security vulnerabilities. Through static analysis methods, the study examined security parameters such as weak encryption, SSL bypass, dangerous permissions, and hidden secret detection, aiming to provide a comprehensive insight into fintech data protection. Research findings revealed that all four applications were at security level four, with security scores ranging from 45-48, which highlighted significant security improvements for ShopeePay and DANA from the previous year, while OVO and GoPay showed minimal changes, underscoring the importance of continuous enhancement in digital financial application security.